Menerapkan Kualifikasi Kepemimpinan Hamba menurut Injil Markus bagi Gembala Sidang GPdI Wilayah Waropen Barat, Papua - Dorus Dolfinus Buinei (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2020)
The church faces great challenges in terms of human resources and its organization, as well as the degradation of quantity and quality. The leadership of a pastor is one of the factors needed to face the challenges of the church. One form of leadership needed is a servant leadership model. The Gospel of Mark gives four important qualifications about servant leadership that Jesus had. The problem is, not many pastors have the qualifications. This article aims to provide an understanding of the pastors of the GPdI congregation in the West Waropen region about the qualifications of Jesus' leadership as servants according to the Gospel of Mark, so that it can be applied in the ministry of pastors in the GPdI West Waropen Region, Papua.AbstrakGereja menghadapi tantangan yang besar dari segi sumber daya manusia dan organisasinya, serta degradasi kuantitas dan kualitas. Kepemimpinan seorang gembala sidang merupakan salah satu faktor yang dibutuhkan untuk menghadapi tantangan gereja. Salah satu bentuk kepemimpinan yang dibutuhkan adalah model kepemimpinan hamba. Injil Markus memberikan empat kualifikasi penting tentang kepemimpinan hamba yang dimiliki Yesus. Persoalannya, belum banyak para gembala sidang yang memiliki kualifikasi tersebut. Artikel ini bertujuan untuk mem-berikan pemahaman para gembala sidang GPdI wilayah Waropen Barat tentang kualifikasi kepemimpinan Yesus sebagai hamba menurut Injil Markus, sehingga dapat menerapkannya dalam pelayanan para gembala jemaat di GPdI Wilayah Waropen Barat, Papua.